Metabolit Sekunder Bacillus sp. sebagai Antijamur Jamur Patogen Tular Benih pada Benih Jagung dengan Metode Uji Blotter - Setyowati, Laras; Purnawati, Arika; Mujoko , Tri; Mukaromah, Fathul (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
Background: Seed is a planting material that must have high viability and quality, including being free from pathogens. One of the obstacles in the supply of quality maize seeds is seed-borne fungal pathogen which can affect the quality of maize seeds and cause plant disease. Endophytic bacteria Bacillus sp. has been widely studied to be able to produce secondary metabolites as antifungals. This study aimed to determine the exact concentration of secondary metabolites of endophytic bacteria Bacillus sp. to decrease the infections of seed-borne pathogens fungal on maize seeds using the blotter test method. Methods: This study used a completely randomized design with four concentration levels (10%, 15%, 20%, 25%) and two strain codes of endophytic bacteria Bacillus sp. (Bth-31a and Bth-22). Results: The result of identifying seed-borne fungal pathogen on maize seed included Fusarium sp., Aspergillus flavus, Aspergillus niger, and Rhizopus sp. The Bth-22 treatment with a concentration of 25% could decrease the infection of seed-borne fungal pathogen and had the highest percentage until 50% compared to the control. While the lowest percentage to decrease the infections of seed-borne fungal pathogen occurred in the Bth-31a treatment with a concentration of 10%, which was 32.1% compared to the control. Conclusions: All seed treatments that used secondary metabolites of Bacillus sp. able to decrease the infections of seed-borne fungal pathogen on maize seed compared to the control. In addition, the treatment of secondary metabolites Bacillus sp. is able to increase the germination of maize seeds.